Enhanced oriented oxidation of medium and long chain alkanes by inactivating hydrophilic organics of soil organic matter - Xu, Jinlan; Li, Huan; Wang, Manman; Cao, Zezhuang; Dai, Jianan; Gao, Mengzhen; Liu, Chuanyu (Journal of environmental chemical engineering, 2024)
Aiming to explore the effect of deactivation of soil organic matter (SOM) on the oriented oxidation of n-alkanes, the petroleum-contaminated soil was pretreated with K2HPO4, and then the soil was treated with Fenton oxidation. After the soil was regulated by K2HPO4, the hydrophilic organics (Protein II and Humic acid-like) in SOM were deactivated, which made the ·OH transfer to oxidize TPH, to achieve efficient oriented oxidation of TPH. After the passivation of hydrophilic organics, the TPH oxidation amount of the efficient group was as high as 6007 mg/kg, which was 1.57 times than unregulated group. In efficient oriented oxidation group, the TPH oriented oxidation amount reached 2186 mg/kg, and the TPH oxidation amounts of unit hydroxyl strength reached 759.42 mg/kg, and the oxidation effect of the medium and long chain alkanes was improved. The results showed that 22.60 % ·OH was transferred to TPH, and the relative reactivity coefficient increased from 0.7 to 1.8(with k>1), which was the reason for improving the oriented oxidation effect of medium and long chain alkanes. It was also found that the two hydrophilic organics had high correlations with TPH oxidation (R2 = 0.9). Further analysis found that the passivation of hydrophilic organics was mainly through the reaction of PO43- with protein and humus in soil organic matter. In general, this study greatly reduced the ineffective consumption of ·OH by SOM, thereby improving the utilization efficiency of H2O2 and realizing the efficient oriented oxidation of petroleum hydrocarbons, which provided great reference value for practical engineering applications. [Display omitted] •Relative reactivity coefficient could increase by inactivating hydrophilic organics.•The allocation of ·OH was affected by Protein II and Humic acid-like.•The higher the ·OH transfer ratio, the higher the TPH oriented oxidation amounts.